235 GHz on‐chip antenna with miniaturised AMC loading in 65 nm CMOS. Issue 5 (12th March 2018) - Zhu, Hua; Li, Xiuping; Feng, Weiwei; Xiao, Jun; Zhang, Jianhua
Abstract : In this study, an on‐chip antenna with miniaturised artificial magnetic conductor (AMC) structure loading is designed and fabricated in the 65 nm complementary metal oxide semiconductor process at 235 GHz. The proposed on‐chip antenna consists of a double‐layer dipole and miniaturised AMC with wide bandwidth and low‐backward radiation. A quarter square loop structure for the miniaturised AMC is designed and analysed by the current and electric field distributions. The simulation results show that the miniaturised AMC has a similar resonant frequency and lower reflection loss compared with the original one. The die area of the proposed antenna is 250 × 410 μ m 2 . The measurement of the −10 dB impedance bandwidth is 81 GHz (200–281 GHz). The gain of the antenna is up to 0 dBi at 235 GHz. By loading the miniaturised AMC, the on‐chip antenna can obtain higher gain, wider bandwidth than that loading the original one. Good agreement can be well observed between the simulated and measured results.